Cr(13)Ni(5)Si(2)-Based Composite Coating on Copper Deposited Using Pulse Laser Induction Cladding - Wang, Ke (Materials (Basel), 2017)
A Cr(13)Ni(5)Si(2)-based composite coating was successfully deposited on copper by pulse laser induction hybrid cladding (PLIC), and its high-temperature wear behavior was investigated. Temperature evolutions associated with crack behaviors in PLIC were analyzed and compared with pulse laser cladding (PLC) using the finite element method. The microstructure and present phases were analyzed using scanning electron microscopy and X-ray diffraction. Compared with continuous laser induction cladding, the higher peak power offered by PLIC ensures metallurgical bonding between highly reflective copper substrate and coating. Compared with a wear test at room temperature, at 500 °C the wear volume of the Cr(13)Ni(5)Si(2)-based composite coating increased by 21%, and increased by 225% for a NiCr/Cr(3)C(2) coating deposited by plasma spray. This novel technology has good prospects for application with respect to the extended service life of copper mold plates for slab continuous casting.